Use of Applications in Football Drills Training in The Covid-19 Pandemic - Adhe Saputra; Ahmad Muzzafar; Ilham Arvan Junaidi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
Covid-19 outbreak has make situation for a lot of difficult people. one the party who experienced it are athletes and coaches football, especially in the training process. The implementation of physical distancing makes state Becomes everything no easy for athletes and coaches in the training process. Restrictions meeting physicall , both on the field and in places other feel has Becomes obstacles in the training process . Performance football jambi not yet can said satisfying Thing this be marked with the difficulty province jambi compete leveled national as well as regional and minimal player football origin jambi career professional level. Certain many factor reason the difficulty province jambi for achievers start from not yet maximum management team since from ssb up to the club level local in manage administration nor develop an exercise program. Plus again with existence plague this covid-19 pandemic make clubs in jambi difficulty in carry out the training process.